2010
DOI: 10.1259/dmfr/19728573
|View full text |Cite
|
Sign up to set email alerts
|

Orthokeratinized odontogenic cyst: a systematic review

Abstract: Objectives: The aims of the review were to evaluate the principal clinical and conventional radiographic features of orthokeratinized odontogenic cyst (OOC) by systematic review (SR), and to compare the frequency of OOC between four global groups. Methods: The databases searched were the PubMed interface of MEDLINE and LILACS. Only those reports of OOCs that occurred in a consecutive series of OOCs in the reporting authors' caseload were considered. Results: 37 reports on 36 case series were included in the SR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
65
0
4

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(79 citation statements)
references
References 44 publications
10
65
0
4
Order By: Relevance
“…It occurs in the jaw bones and about 1/2 to 2/3 of the cases have been reported to be associated with an impacted tooth [3,8], or have presented clinically as dentigerous cysts [5]. Sporadic OOC has been recently reported to be associated with two supernumerary teeth [9].…”
Section: Discussionmentioning
confidence: 99%
“…It occurs in the jaw bones and about 1/2 to 2/3 of the cases have been reported to be associated with an impacted tooth [3,8], or have presented clinically as dentigerous cysts [5]. Sporadic OOC has been recently reported to be associated with two supernumerary teeth [9].…”
Section: Discussionmentioning
confidence: 99%
“…43 Like the ameloblastoma, the lingual cortex of OOCs expands down past the otherwise unaffected lower border of the mandible. 44 Unlike KCOTs 21 and ameloblastoma, 37,38 OOCs have so far not exhibited root resorption. 43,44 What to do with the mixed parakeratoticeorthokeratotic lesions that are neither wholly KCOT nor wholly OOC?…”
Section: Distinguishing Between a Kcot And A Ooc Radiologicallymentioning
confidence: 99%
“…This is now called the orthokeratinised odontogenic cyst (OOC). 43,44 Recently it was shown that the KCOT and OOC differ radiologically. 43 Although multiple OOCs 45 unaccompanied by features suggestive of NBCCS have been reported, it should be reiterated that there are cases of multiple KCOTs that are also not accompanied by NBCCS features, particularly in East Asians.…”
Section: Kcotmentioning
confidence: 99%
“…Complications can occur, such as infection, mandibular fracture, or encroachment upon the maxillary sinus or the nasal cavity. Possible signs are swelling with or without pain and loosening or displacement of teeth [8][9][10].…”
Section: Diagnosismentioning
confidence: 99%
“…In this imaging modality, cysts of the jaws appear as sharply delineated radiolucencies. In the case of infection, the margin can appear blurred [7,8]. Modern techniques, such as computed tomography (CT), magnetic resonance imaging (MRI), or cone beam CT, can sometimes yield additional information about the cyst's size and relationship to endangered structures.…”
Section: Diagnosismentioning
confidence: 99%